Faktor Non Makanan yang Berhubungan dengan Kejadian Stunting pada Anak Balita - Londok, Rara; Munthe, Deviana P.; Bawiling, Nancy S. (Yayasan Syalom Cipta Sumikolah, 2025)
Stunting is a condition in which toddlers consistently grow poorly due to prolonged malnutrition and frequent illness. This condition disrupts physical growth and brain development, increases the risk of disease in adulthood, and reduces work ability. This study aims to analyze non-dietary factors associated with stunting in Kotabunan District, East Bolaang Mongondow Regency. The study was conducted quantitatively and used a cross-sectional design. Seventy-nine toddlers aged 24 to 59 months and their mothers or caregivers were randomly selected. Data were collected through a questionnaire that had been tested for validity and reliability, as well as data from the Child Health Card (KMS) and community health center records. Data were analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) methods. The chi-square test results showed a significant association between maternal education level (p=0.035), child vaccination status 0,002 access to health services (p=0.031), environmental sanitation conditions (p=0.018), and birth spacing (p=0.008) and stunting.